Delayed diagnosis of T3 supplementation in a bodybuilder presenting with tachycardia and features of sepsis. Issue 1 (13th January 2020) - Warner, Bronwen E; Woodrow, Charles J; Pal, Aparna
Abstract : A 25-year-old man presented generally unwell to the emergency department. Initial assessment identified systemic inflammatory response syndrome markers with an insect bite as a potential source of infection and he was treated for presumed sepsis. Tachycardia persisted and baseline thyroid function testing showed undetectable free thyroxine and thyroid-stimulating hormone (TSH), prompting further endocrine investigation. Triiodothyronine (T3) was markedly raised with normal TSH receptor antibodies, and the patient later confessed to supplementary testosterone and T3 use as part of bodybuilding activities. Following counselling, thyroid function normalised and the patient returned to his usual health. This case describes the diagnostic work up in a case of persistent tachycardia caused by T3 supplementation, demonstrating the potential for endocrine supplementation by bodybuilders which may be poorly understood and recognised by clinicians. T3 supplementation should be considered and a thorough drug history obtained in bodybuilders presenting with symptoms of thyrotoxicosis and deranged thyroid function tests.